Dynamic Editorial Visual Identity and cover design: the case of La Luna de Metrópoli (2018-2020) - Martín-Sanromán, Juan-Ramón (2022)
Editorial Visual Identity is a branch of visual identity that refers to the symbolic translation of the personality of publications, products in whose strategy the covers have a special relevance as the main showcase of the content and an essential factor in the marketing of the medium. On the other hand, contemporary branding reveals a significant focus on dynamic identities, a phenomenon that proposes a more flexible use of the features that define their respective graphic programs. In this context, this research seeks to analyze the key features of the Dynamic Visual Identity in the editorial field -Dynamic Editorial Visual Identity (DEVI)- and illustrate this strategy by focusing on the covers of La Luna de Metrópoli (a weekly newspaper supplement that has won multiple awards due to its visual and creative excellence) as a case study. With a sample of 96 pieces designed between 2018 and 2020 -when its printed edition is discontinued-, four variables are analyzed: the changes of the headboard, the design, the contents and the use of rhetorics in the covers (as visual texts). Among its conclusions, the article reveals the important presence of rhetorical figures -and, especially, metaphors- in the identity of a publication defined by the mutability of its headboard and the stylistic heterogeneity of its covers.